Strategies of Islamic Education Teachers in Facing The Current of Modernity at SMPIT Al-Uswah Magetan: A Qualitative Study - Hamidah Ayu Pramesti Toana; Mohammad Zakki Azani (FKIP - Universitas Riau, 2026)
This study explores the strategies employed by Islamic Religious Education teachers in responding to the challenges of modernity at SMPIT Al-Uswah Magetan, an integrated Islamic junior high school in Indonesia. The study was conducted in the context of increasing exposure to digital technology, globalization, and social change that influence students’ learning behavior and religious character. Using a descriptive qualitative approach, data were collected through in-depth interviews with Islamic Religious Education teachers and the school principal, classroom observations, and document analysis. The findings show that teachers apply several empirically observed strategies, including regulating students’ use of digital devices during school hours, strengthening religious literacy through Qur’an reading and discussion activities, providing regular spiritual guidance through worship practices, maintaining collaboration with parents and external institutions, and demonstrating exemplary behavior in daily interactions. The study also identifies supporting factors such as a religious school environment, leadership support, and teacher commitment, as well as constraints including social media influence, limited parental involvement, and diverse student backgrounds. These findings indicate how Islamic Religious Education teachers adapt instructional and character-building practices to maintain Islamic values within a modern educational setting.